7.01.004: Comic strip re: computers with caption "No problem, Don Walsh will know what to do," commissioned by Sheila Lynch - Tennant, Rich
Sheila Lynch gave me this with a gift one year. This items is a Rich Tennant cartoon to which Sheila M.P. Lynch has added her own caption.